Surgical Outcomes of Primary Congenital Glaucoma in Children Under One Year from the Nile Delta - Farid MF (Dove Medical Press, 2021)
Mohamed F Farid, Mohamed Anany, Mohamed A Awwad Ophthalmology Department, Benha University, Benha, EgyptCorrespondence: Mohamed A AwwadOphthalmology Department, Benha University, PO Box: 13511, 1 Fareed Nada Street, Benha, EgyptEmail mohdzahir82.ma@gmail.comPurpose: To present outcomes of surgical management of primary congenital glaucoma (PCG) in children less than one year of age in a population based at the Nile Delta.Methods: A retrospective review of medical records of patients with PCG less than one year of age at presentation who underwent surgical intervention in a tertiary care facility based at the Nile Delta. All patients underwent measurement of intraocular pressure (IOP), horizontal corneal diameter (HCD), cup-to-disc ratio (CDR) before and after surgery and a minimum of 6 months follow up was required. Surgical success was defined as IOP less than 22mmHg without medications and without progression of main disease parameters.Results: The review revealed 44 eyes of 26 consecutive patients who underwent surgical treatment for PCG. Average age at surgery was 5.2 months and mean follow up was 18.5 months. Preoperative IOP was 28.5± 4 mmHg, HCD was 13.7± 0.7mm, and CDR (when visible) was 0.65± 0.18. A total of 69 surgical procedures were performed with an average of 1.56 procedures per eye. Postoperative IOP was 13.3± 4.8 mmHg, HCD was 12.8± 0.9mm, and CDR was 0.3± 0.2 (P< 0.0001). Surgical success was achieved in 32 eyes (72.7%) while sight-threatening postoperative complications were reported in 3 eyes.Conclusion: Surgical management of PCG younger than one year of age achieved good success rate in the region of the Nile Delta with low rate of visually significant postoperative complications. However, larger studies with longer follow up are needed to fully reveal the overall characteristics of PCG in the region.Keywords: primary congenital glaucoma, intraocular pressure, trabeculotomy, trabeculectomy, Ahmed glaucoma valve, the Nile Delta